PERKECAMBAHAN BENIH SENGON (Paraserianthes falcataria) MENGGUNAKAN MEDIA PASIR SUNGAI KUANTAN DENGAN PASIR SUNGAI MUARA (ANAK SUNGAI) DI KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Rofi Julianda; M. Mardhiansyah M. Mardhiansyah; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Paraserianthes falcataria is a plant which has fast growing species. Sand is one of seedling media are often used to replace the function of the ground. Although sand is poor nutrien, it not affects seed germination of Paraserianthes falcataria because in the process of germination is not necessary nutrient but medium condition with capable of providing water and breathing the seeds. This research aims to understand germination growth and the best of seedling media in germination growth of Paraserianthes falcataria. The research activities carried out at Forestry Laboratory and Experimental Forestry Unit Agriculture Faculty, University of Riau, Pekanbaru. This reasearch was conducted during 1 month, in September-October 2016. The experimental design used in this research is completely randomized design (CRD) method. Composed of 3 treatments, each treatment consisted of 3 replications and use 50 seeds sengon, with total number of sengon seed 450 grains. The result shows that sand medium of kuantan river (P1), river estuary (P2) and Kuantan river + river estuary (P3) used not differ from germination of Paraserianthes falcataria. All types of sand can be used as a medium for germination of Paraserianthes falcataria